(untitled) (International conference on multidisciplinary science, 2024)
The healing powers of nature are known to almost all people. In addition, lectures, talks, special broadcasts and shows are conducted on water, air, sun and environmental ecology. Mass media are constantly covering natural landscapes in the republic’s territories, experiences in using them for health, and events. Based on these, some arguments can be made about the scientific foundations related to the healing powers of nature.